2016
DOI: 10.1371/journal.pone.0156506
|View full text |Cite
|
Sign up to set email alerts
|

Retention of HIV-Infected Children in the First 12 Months of Anti-Retroviral Therapy and Predictors of Attrition in Resource Limited Settings: A Systematic Review

Abstract: Current UNAIDS goals aimed to end the AIDS epidemic set out to ensure that 90% of all people living with HIV know their status, 90% initiate and continue life-long anti-retroviral therapy (ART), and 90% achieve viral load suppression. In 2014 there were an estimated 2.6 million children under 15 years of age living with HIV, of which only one-third were receiving ART. Little literature exists describing retention of HIV-infected children in the first year on ART. We conducted a systematic search for English la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
43
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 52 publications
9
43
3
3
Order By: Relevance
“…A systematic review of retention outcomes of children in the first year of ART in resourcelimited settings reported that younger age (<1 year) was associated with poorer retention among children in HIV care. [13] Similar findings were described in a report of birth HIV diagnosis with ART initiation within the first month of life at a single site in SA. [14] These findings have serious policy implications for SA, where current guidelines recommend birth testing for all HIV-exposed children.…”
Section: Researchsupporting
confidence: 84%
“…A systematic review of retention outcomes of children in the first year of ART in resourcelimited settings reported that younger age (<1 year) was associated with poorer retention among children in HIV care. [13] Similar findings were described in a report of birth HIV diagnosis with ART initiation within the first month of life at a single site in SA. [14] These findings have serious policy implications for SA, where current guidelines recommend birth testing for all HIV-exposed children.…”
Section: Researchsupporting
confidence: 84%
“…This was very similar to findings from South Africa (Sengayi et al, 2013) which showed 90% retention after 12 months of follow-up in 2013. Studies from across Africa, estimated a median pediatric retention in care for 12 months after treatment initiation to be 82.6%, with a range of 71-95% (Abuogi et al, 2016). Although some studies differ in the follow-up periods, the rates of retention are fairly similar our study.…”
Section: Discussionsupporting
confidence: 64%
“…However, globally only 43% of children living with HIV received ART in 2016 [2] and the attrition (loss to follow-up and/or death) of children on ART is higher in resource limited settings when compared to developed countries [3,4]. Many studies in Africa and Asia have shown that it is challenging to enrol and retain paediatric patients on ART care [57]. A study from South Africa showed that only 71% of HIV-positive infants were linked to HIV care [8].…”
Section: Introductionmentioning
confidence: 99%
“…A couple of studies using adult HIV seropositive patient data (aged ≥ 15 years of age) from IHC programme have shown that the attrition rates in pre-ART care and ART care is 32% and 16%, respectively (5-year cohort analysis with 13.7 months median duration of follow-up) [5,11]. Compared to these results, private sector adult ART cohort in Myanmar had a relatively higher attrition rate of 20% during 5-years follow-up [12].…”
Section: Introductionmentioning
confidence: 99%